MicroRNA-19b predicts widespread pain and posttraumatic stress symptom risk in a sex-dependent manner following trauma exposure. Issue 1 (January 2020) - Linnstaedt, Sarah D.; Rueckeis, Cathleen A.; Riker, Kyle D.; Pan, Yue; Wu, Alan; Yu, Shan; Wanstrath, Britannia; Gonzalez, Michael; Harmon, Evan; Green, Paul; Chen, Chieh V.; King, Tony; et al.
Abstract : Abstract: Posttraumatic widespread pain (PTWP) and posttraumatic stress symptoms (PTSS) are frequent comorbid sequelae of trauma that occur at different rates in women and men. We sought to identify microRNA (miRNA) that may contribute to sex-dependent differences in vulnerability to these outcomes. Monte Carlo simulations (x10, 000) identified miRNA in which predicted targeting of PTWP or PTSS genes was most enriched. Expression of the leading candidate miRNA to target PTWP/PTSS-related genes, miR-19b, has been shown to be influenced by estrogen and stress exposure. We evaluated whether peritraumatic miR-19b blood expression levels predicted PTWP and PTSS development in women and men experiencing trauma of motor vehicle collision (n = 179) and in women experiencing sexual assault trauma (n = 74). A sex-dependent relationship was observed between miR-19b expression levels and both PTWP (β = −2.41, P = 0.034) and PTSS (β = −3.01, P = 0.008) development 6 months after motor vehicle collision. The relationship between miR-19b and PTSS (but not PTWP) was validated in sexual assault survivors (β = −0.91, P = 0.013). Sex-dependent expression of miR-19b was also observed in blood and nervous tissue from 2 relevant animal models. Furthermore, in support of increasing evidence indicating a role for the circadian rhythm (CR) in PTWP and PTSS pathogenesis, miR-19b targets were enriched in CR gene transcripts. Human cohort and in vitro analyses assessing miR-19b regulation of key CR transcripts, CLOCK and RORA, supported the potential importance of miR-19b to regulating the CR pathway. Together, these results highlight the potential role that sex-dependent expression of miR-19b might play in PTWP and PTSS development after trauma/stress exposure. Abstract : Supplemental Digital Content is Available in the Text.Translational research approaches identified miR-19b as a potential miRNA regulatory hub for posttraumatic widespread pain and posttraumatic stress symptoms that is expressed differently in males and females after trauma/stress exposure